Dekolagenasi Limbah Tulang Paha Ayam Broiler (Gallus domesticus) oleh Natrium Hidroksida (NaOH) untuk Penentuan Kadar Kalsium (Ca) dan Fosfat (PO4) - Sitti Musdalifah; Syamsidar HS; Suriani Suriani (Al-Kimia, 2016)
This research aims to determine the level of Calcium (Ca) and Phosphate (PO4), and the influence of broilers femur submersion in NaOH toward Calcium (Ca) and Phosphate (PO4) levels. The method used in this research is decollagenation of broilers (Gallus domesticus) femur. Then, the parameters observed are chemical tests of Calcium (Ca) and Phosphate (PO4) levels. Decollagenation treatment was carried out in three soaking-time variation such as 42 hours, 72 hours, and 96 hours to respectively determine the Calcium and Phosphate levels. The result shows that soaking-time of femur does not give significant effect to increased levels of Calcium (Ca) and Phosphate (PO4).